1998
DOI: 10.1021/bp980066m
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Dissociation of Antigen-Antibody Complexes

Abstract: Pressures on the order of 1000-4000 bar have been reported to reversibly dissociate a number of oligomeric protein complexes without gross changes in protein structure. Here, we report that hydrostatic pressure can also dissociate some antigen-antibody complexes in solution. The association of fluorescent-labeled antigens with monoclonal antibodies was monitored via increases in the fluorescence anisotropy upon binding. Previously, we had found that pressures of 2000 atm were able to dissociate bovine serum al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…The quenching decreased with pressure as seen in the figure. In the previous paper [24], we have calculated the standard volume change associated with the dissociation of FL and IgG-49 from the FL-IgG-49 complex and obtained the value of −5.2 cm 3 mol −1 , that is, the complex expands slightly by binding of them. Similar dissociation behavior of anti-fluorescyl [25][26][27] and anti-BSA [28] monoclonal antibodies by pressure has been observed, and our value is close to the value reported for the anti-fluorescyl monoclonal antibody with a strong affinity to FL by Herron et al [15]. The value decreased with increasing temperature.…”
Section: Pressure Effect On the Interaction Of Igg-49 With Inhibitorssupporting
confidence: 91%
“…The quenching decreased with pressure as seen in the figure. In the previous paper [24], we have calculated the standard volume change associated with the dissociation of FL and IgG-49 from the FL-IgG-49 complex and obtained the value of −5.2 cm 3 mol −1 , that is, the complex expands slightly by binding of them. Similar dissociation behavior of anti-fluorescyl [25][26][27] and anti-BSA [28] monoclonal antibodies by pressure has been observed, and our value is close to the value reported for the anti-fluorescyl monoclonal antibody with a strong affinity to FL by Herron et al [15]. The value decreased with increasing temperature.…”
Section: Pressure Effect On the Interaction Of Igg-49 With Inhibitorssupporting
confidence: 91%
“…Therefore, in this pressure range, it should be feasible to disrupt antigen–V H H complexes without unfolding either molecule. This strategy can be advantageously used for immunoaffinity separation, where a specifically bound antigen is eluted from the immunoadsorbent after a controlled pressure increase (Olson et al 1989; Sudaram et al 1998). Compared with the harsh conditions usually used, such a “hyperbaric elution” extends the immunoadsorbent lifetime (Olson et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The rates were evaluated by fitting the data to either mono-or biexponential equations: 3 , respectively. The independent variable Y was the observed scattering intensity in counts/s after subtracting the scattering due to buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Their quaternary structures are crucial to the mechanism of chaperoninassisted protein folding. These two proteins are coexpressed from a common GroE operon in Escherichia coli (1)(2)(3). Mutational studies have demonstrated that both chaperonins are essential for protein folding in vivo (4 -6).…”
mentioning
confidence: 99%